Morphology of the murine choroid plexus: Attachment regions and spatial relation to the subarachnoid space - Theresa Greiner; Katerina Manzhula; Louise Baumann; Hannes Kaddatz; Jens Runge; Jens Runge; Jonas Keiler; Markus Kipp; Sarah Joost (Frontiers Media S.A., 2022)
The choroid plexus has recently been identified as a possible migration route for peripheral immune cells into the central nervous system. For future investigation of this route, profound knowledge of the morphology of the murine choroid plexus is a prerequisite. We here present a detailed morphological description of the murine choroid plexus, its attachment regions as well as its spatial relation to the subarachnoid space. We used micro-computed tomography of immersion-contrasted fixated brains to generate three-dimensional models of the ventricle system and the choroid plexus and aligned micro-computed tomography-based sections with histological paraffin-embedded sections after immunohistochemical labeling of the basal lamina and choroid plexus epithelium marker proteins (laminin and aquaporin 1). The murine choroid plexus is located in all four ventricles and is attached to the brain parenchyma in narrow attachment regions with a specific morphology in each ventricle. While in the lateral and fourth ventricle, the attachment site is formed by thin tissue bridges, the choroid plexus attachment in the third ventricle has a more complex V-like shape. In all ventricles, the choroid plexus is in close spatial relationship with the subarachnoid space that extends from the brain surface along physiologic openings toward the choroid plexus. In summary, we here provide a description of the morphology of the murine ventricle system and choroid plexus, the attachment regions of the choroid plexus and its connection to the subarachnoid space, as well as a three-dimensional model of the ventricles, the choroid plexus, and the subarachnoid space to facilitate a spatial understanding of these complex structures.